PENINGKATAN KUALITAS LAYANAN DALAM USAHA BENGKEL SEPEDA MOTOR DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DAN PERENCANAAN PENGEMBANGAN STRATEGI - Muhammad Choirul Nisyam (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2013)
In developing a business workshop , garage entrepreneurs should be able menyesesuaikan general desire among consumers maintain quality , trust, loyalty and closeness with konsumen.Menggaris underscore the problems above , the need for a study to determine the direction of what are the attributes for desired by consumers terhada workshop JAYA MEKAR motors in kaitanya proposals for improving the quality and strategi.Salah one method that can capture the desires of consumers is Funcyion quality Deployment ( QFD ) Yag tool used to analyze customer need , and to know the SWOT Strengths , Weaknesses , opportunuties , Threats and strategies for the SWOT matrix SO ( Strength and Opportunities) , WO ( Weaknesesse and Opportunities) , ST ( Strength and Threats ) , and WT ( Weaknesess and Threats ) . Technical response in improving the quality of the bike shop on the House OF MEKAR JAYA Capacity Building Technical quality is the mechanical application of SOS ( service Operations , Done quickly and accurately , Development of communication skills , consistently 5S Implementation , leisure lounge area to relax , minimum stock Standardization spear parts , addition Free Hotspot area , fan , toilet , music , parts handling claims Development , Implementation and competition mechanical competence , Network Development authorized workshops , implementation of marketing programs servicing , workshop equipment Standards